2015
DOI: 10.1039/c5ra09469k
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of nitrate ions from water using hybrid Al2O3/bio-TiO2nanocomposite impregnated thermoplastic polyurethane nanofibrous membrane

Abstract: In the present study, we have exploited the nitrate adsorption property of Al2O3/bio-TiO2 nanocomposite (ABN) and ABN impregnated electrospun thermoplastic polyurethane nanofibrous membrane (ABN/TPU-NFM) for water purification. Nitrate adsorption was investigated both in batch and dip mode studies. Parameters like effect of contact time, adsorbate concentration and membrane size were optimized. The adsorption capacity (Q0) of the ABN and ABN/TPU-NFM was found to be 30.3 and 14.9 mg/g, respectively. Kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The dramatic improvement in the adsorption was attributed to the electrostatic interaction between the anions and positively charged sites on the surface of the acid-treated carbon cloth, as the distilled water-treated carbon cloth adsorbed 5 and 20 times less of NO3and NO2 -, respectively, compared to the former (Afkhami et al, 2007). In a very recently reported work, a similar scenario was also observed where NO3adsorption was enhanced due to involvement of the surface OHgroups by bridging between NO3and metal oxide surfaces (Suriyaraj et al, 2015). Therefore, as revealed from the literature, the high uptake of oxalic acid than nitrate by carbon based TiO2,…”
Section: Adsorption Isotherms Of Nitrate and Oxalic Acidsupporting
confidence: 58%
“…The dramatic improvement in the adsorption was attributed to the electrostatic interaction between the anions and positively charged sites on the surface of the acid-treated carbon cloth, as the distilled water-treated carbon cloth adsorbed 5 and 20 times less of NO3and NO2 -, respectively, compared to the former (Afkhami et al, 2007). In a very recently reported work, a similar scenario was also observed where NO3adsorption was enhanced due to involvement of the surface OHgroups by bridging between NO3and metal oxide surfaces (Suriyaraj et al, 2015). Therefore, as revealed from the literature, the high uptake of oxalic acid than nitrate by carbon based TiO2,…”
Section: Adsorption Isotherms Of Nitrate and Oxalic Acidsupporting
confidence: 58%
“…Recently, a hybrid Al 2 O 3 /bio-TiO 2 nanocomposite was prepared by our group and further impregnated into a thermoplastic polyurethane (TPU) nanobrous membrane and studied for its efficiency for uoride removal from an aqueous solution using a dip mode adsorption method. 68 The adsorption capacities (Q 0 ) of the nanocomposite and the nanocomposite impregnated TPU nanober were found to be 2.73 and 1.9 mg g À1 respectively. This facile approach of designing nanocomposite impregnated nanober membranes can be used for F À removal from drinking water.…”
Section: Polymer Carbon and Hydroxyapatite Based Nanomaterialsmentioning
confidence: 96%
“…This showed efficient filtration of organic dyes and carcinogenic ions such as arsenic and even TiO2 nanoparticles from the water. A nontoxic alumina/titanium oxide composite with PU electrospun fibers formed via electrospraying silanes have also been shown to be able to remove fluoride ions from water with high adsorption capacity [53]. Additionally, studies were conducted with this kind of composite, and it was observed that it is also effective in removing nitrates from aqueous media.…”
Section: Poly (Vinylidene Fluoride)mentioning
confidence: 99%